Water-Assisted Co-Injection Molding of Non-Circular Tubes. Issue 4 (May 2019) - Kuang, T Q; Xu, P; Feng, Q; Turng, L S
Abstract: Water-assisted co-injection molding (WACIM) is a complex and creative injection molding process. A three-dimensional model for WACIM was setup and a k – ω turbulence model was adopted to deal with the turbulent flow of the water. The volume of fluid (VOF) method was used to track the moving interfaces of the skin–inner melt and the inner melt–water. Numerical simulations for the filling stage of WACIM parts with four types of cross-sections were carried out with the computational fluid dynamics (CFD) method. Experiments were conducted to verify the simulation results. The results of the experiments were in agreement with those of the simulations. The cross-section shape of the cavity had a significant effect on the penetrating area of the inner melt, while the shape of the water permeation eventually becomes round. The penetration area of the water increased in the flow direction, and the residual wall thicknesses of the inner melt downstream was thinner than the melt upstream.